A new genus and species of abyssal sponge commonly encrusting polymetallic nodules in the Clarion-Clipperton Zone, East Pacific Ocean. Issue 6 (2nd November 2017) - Lim, Swee-Cheng; Wiklund, Helena; Glover, Adrian G.; Dahlgren, Thomas G.; Tan, Koh-Siang
Abstract : The Clarion-Clipperton Zone (CCZ) in the East Pacific is a vast region targeted for deep-sea mineral exploration, for which there are almost no published taxonomic data. Here we describe Plenaster craigi gen. nov. sp. nov. from depths of ∼4000 m in the eastern CCZ polymetallic nodule province. Despite over 40 years of intense exploration in the area, we reveal that P. craigi sp. nov. is the most abundant sponge and the most common metazoan encrusting on nodules in our study area at the eastern CCZ. It has a mean abundance of 15.3 ± 8.9 individuals per m 2 across 11 stations in a 30 × 30 km study site nested within the Singapore exploration area. The white encrusting sponge is filled with spheroxyasters with occasional styles protruding the surface. Plenaster craigi sp. nov. is morphologically similar to genera from three different families in two orders: Timea (Timeidae; Tethyida); Hemiasterella and Leptosastra (Hemiasterellidae; Tethyida); and Paratimea (Stelligeridae; Axinellida). However, based on the molecular (COI and 28S) phylogenetic trees generated in this study, P. craigi sp. nov. was located in the Order Axinellida and appeared to be distant to Timea, Hemiasterella, Leptosastra, and Paratimea . We propose a new genus for our material to be placed provisionally in the family Stelligeridae, as it is the only family in the order Axinellida whose members possess euasters. This provisional placement may change when sequences of the type specimens of these genera and advanced phylogenetic reconstruction methods become available in the future. However, we have shown clearly that Plenaster gen. nov. is unique and distinct from all currently known taxa. Plenaster craigi sp. nov. being an abundant metazoan encrusting on nodule and easily identified filter-feeding animal is a potentially indicator species for future mining impacts in the eastern CCZ, and possibly across the entire CCZ. LSID:urn:lsid:zoobank.org:act:99D2DDBA-4643-4752-8C8A-AFF314E6B6E3